The Influence of Students Motivation Toward Students Achievement - Tuti Alawiyah; Urip Sulistiyo (International Journal of Language Teaching and Education, 2018)
This paper examines the language attitudes of Minangkabau people toward Minangkabau language (MIN) and Indonesian (BI) in West Sumatra, Indonesia. The data were collected in the form of questionnaires, in-depth interviews and participant observation with a sample of 200 Adult respondents in six research areas. This research uses a Likert scale with the categories classified into five alternatives (1 = Strongly Disagree, 2 = Disagree, 3 = Uncertain, 4 = Agree, and 5= strongly agree) and there are some tables analyzed based on yes/no questions, no=0 and yes=1. There are twelve questions on the questionnaire pertaining to the attitudes of adults. The results show that the adult attitudes can be classified into three categories, (1) positive; (2) negative; and (3) ambivalent attitudes. The third category is dominant. The term ‘ambivalent” is used for intermediate results. It is shown that the respondents expressed their feeling in both positive and negative comments in the same utterance when answering the questions related to MIN. For these responses, it is seen that there is a mixed feeling where they use “but” or “although” after expressing their positive feelings thereby countering their first statement. The evidence of the ambivalent and mixed feelings from respondents is shown. This means that Minangkabau people tend to avoid the conflict of having negative opinions; they tend to say what they mean in more indirect ways. On the other side, there is a positive attitude in response to the questions about BI. Majority of respondents have very strong positive attitudes towards BI